Experience of Morphologic Left Ventricle Training in Congenitally Corrected Transposition of the Great Arteries in Children: Evaluation of the Operation Results - Olena V. Stohova (Український журнал серцево-судинної хірургії, 2024)
The aim. To evaluate the efficacy of morphologic left ventricle (mLV) training through pulmonary artery banding (PAB) in pediatric patients with congenitally corrected transposition of the great arteries.